2016
DOI: 10.4236/jsea.2016.912039
|View full text |Cite
|
Sign up to set email alerts
|

Internet Usage, Challenges, and Attitudes among University Students: Case Study of the University of Jordan

Abstract: The Internet usage has grown rapidly during the last decade in almost every country in the world and in Jordan specifically; today millions of individuals are connected to the Internet and the Internet has become the backbone of the information economy. It was used for social, commercial, political, and personal interactions. This study aims to investigate the attitudes of students at The University of Jordan towards using ICT (Information and Communication Technology). A semi-structured questionnaire was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
3
14
1
Order By: Relevance
“…When the internet usage goals of medical students are examined in the research, it is seen that the most are social media, watching videos, searching for information & studying, playing games, listening to music, voice or video conversation, studying and purchasing products. This finding is consistent with the findings of the studies conducted by Yıldız and Demir (2016), Baker and White (2010), Cheung, Chiu, and Lee (2011), Dikmen and Tuncer (2018), Almarabeh, Majdalawi, and Mohammad (2016). In the research conducted by Oğuz, Zaim, Özel, and Saka (2008) on the cognitive status of medical students on the internet, it was determined that the students mostly used social media.…”
Section: Journal Of Educational Issuessupporting
confidence: 88%
“…When the internet usage goals of medical students are examined in the research, it is seen that the most are social media, watching videos, searching for information & studying, playing games, listening to music, voice or video conversation, studying and purchasing products. This finding is consistent with the findings of the studies conducted by Yıldız and Demir (2016), Baker and White (2010), Cheung, Chiu, and Lee (2011), Dikmen and Tuncer (2018), Almarabeh, Majdalawi, and Mohammad (2016). In the research conducted by Oğuz, Zaim, Özel, and Saka (2008) on the cognitive status of medical students on the internet, it was determined that the students mostly used social media.…”
Section: Journal Of Educational Issuessupporting
confidence: 88%
“…According to table 3, two significant negative attitudes were being lazy and committing plagiarism action that haunted EFL learning. This occurrence was supported by (Brandstrom, 2011) as cited in (Almarabeh et al, 2016) who explained that post-millennial students had the dependence of the prepared information available in the online platforms. That dependence led them into laziness and negative behaviors such as finding a shortcut in achieving their goals.…”
mentioning
confidence: 72%
“…That cheating action is the risk of online search engine usage (Sharples, Graber, Harrison, & Logan, 2009). To be worse, those students do not seem aware that copy-pasting is a kind of crime in the educational setting, which is then becoming the reason in the number of plagiarism cases (Karchmer, 2001).As a result of the ongoing trials, digital native students are having the dependence of the prepared information available in the online platforms (Brandstrom, 2011) as cited in (Almarabeh, Majdalawi, & Mohammad, 2016). This condition forms a dilemmatic setting since there is no simple solution for it (Sharples et al, 2009).…”
Section: Figurementioning
confidence: 99%
“…Other responses regarding the purpose of using mass media in included communicating, accessing information or searching, watching movies or soup operas, having fun/ killing time, watching the news, playing online games, and studying, respectively. Almarabeh, Majdalawi, and Mohammad (2016) also found that students utilized internet mainly for social websites, chatting, and gathering information. Similarly, Bashir, Mahmood and Shafique (2016) found that the highest frequencies for the purpose of using internet belonged to class assignments and research projects, updating knowledge, communication, and entertainment.…”
Section: Discussionmentioning
confidence: 98%